Awareness and perception of pharmacy researchers about conflict of interest: A study from the MENA region - Hadeia Mashaqhbeh, Karem H. Alzoubi, Omar F. Khabour, Rana Abu-Farha (Journal of Applied Pharmaceutical Science, 2022)
The literature has shown some bias in research about the effectiveness and efficacy of medications due to the influence of the pharmaceutical industry. Thus, researchers’ understanding of conflict of interest (COI) is substantial and may influence the quality of scientific research. Therefore, in this study, we aimed to assess pharmacy researchers’ awareness and perception about COI in the Middle East and North Africa (MENA) region and the factors affecting their disclosure of COI. In this cross-sectional study, a convenience sample of pharmacy researchers from the MENA region was surveyed for their awareness and perception about the principles of COI. The questionnaire was divided into three main sections. The first section assesses the demographic information of the study participants; the second section assesses researchers’ awareness and practices in dealing with COI; and, finally, the third section assesses participants’ perception about COI. The questionnaire was uploaded on the Google Forms electronic platform, and it was distributed to the potential study participants via their professional emails. Finally, logistic analysis was used to evaluate predictors affecting COI disclosure by the study participants. A total of 271 pharmacy researchers participated in this study. Researchers were distributed based on their academic rank as follows: 63 professors (23.3%), 59 associate professors (21.8%), 97 assistant professors (35.8%), and 52 lecturers (19.2%). The majority of researchers indicated that they were familiar with the concept of COI (88.9%), and they agreed that the existence of COI should be disclosed by all authors (84.5%). About 33.2% of the study participants did not know if their institution had a policy for COI. About half of the participants (48.70%) believed that disclosure is the only way for the management of COI. However, only 41.7% of them (n = 113) indicated that they had disclosed COI in their published research. Finally, participants who have a collaboration with the industry showed a significantly lower tendency to disclose their COI than those who do not have any partnership with the industry (OR = 0.471, p = 0.017). The majority of the pharmacy researchers from the MENA region are familiar with the principles of COI, but a lower percentage of them disclose their COI in their published research. Efforts should be made to educate researchers about the importance of disclosing COI, which might reduce the potential of bias in their published research.
Keywords: Pharmacy researchers, attitude, conflict of interest, MENA